A compilation of Web-based research tools for miRNA analysis. (25th February 2017) - Shukla, Vaibhav; Varghese, Vinay Koshy; Kabekkodu, Shama Prasada; Mallya, Sandeep; Satyamoorthy, Kapaettu
Abstract: Since the discovery of microRNAs (miRNAs), a class of noncoding RNAs that regulate the gene expression posttranscriptionally in sequence-specific manner, there has been a release of number of tools useful for both basic and advanced applications. This is because of the significance of miRNAs in many pathophysiological conditions including cancer. Numerous bioinformatics tools that have been developed for miRNA analysis have their utility for detection, expression, function, target prediction and many other related features. This review provides a comprehensive assessment of web-based tools for the miRNA analysis that does not require prior knowledge of any computing languages.